Burnout and Turnover among NICU Nurses. Issue 1 (January 2022) - Thomas, Anisa O.; Bakas, Tamilyn; Miller, Elaine; Johnson, Kimberly; Cooley, Heather L. Tubbs
Abstract: Introduction: In 2019, the national average turnover rate of registered nurses in the United States was approximately 17.8%. Each percentage increase in turnover costs a hospital, on average, 270, 800. Although burnout is a known contributor to nurses' turnover intention, few studies have examined the relationship between nurse burnout and turnover, and there is little data on this relationship in neonatal intensive care environments. The purpose of this study was to examine the relationship between nurse burnout and turnover among neonatal intensive care unit (NICU) nurses. Study Design: A secondary analysis of data collected from an observational study involving 136 nurses in a 52-bed NICU from 2013 to 2014. Methods: Multivariate logistic regression models were used to test for associations between measures of burnout and turnover. Results: 16.9% of nurses turned over during the 11 months of the original study. Most nurses reported high (46%) to moderate (37%) levels of emotional exhaustion. Final models did not indicate a relationship between burnout and turnover. Clinical Nursing Implications: Although burnout has been associated with turnover intent among nurses, we did not observe an association between burnout and turnover among NICU nurses. Despite no direct relationship between burnout and turnover in the NICU, burnout may have other negative consequences. Nurse leaders should continue to prioritize reducing burnout among nursing staff to improve the well-being of the NICU nurse workforce. Abstract : Work-related burnout, characterized by emotional exhaustion, depersonalization, and personal accomplishment, has been associated with nurses' intent to leave their job. In this study of nurses in the neonatal intensive care unit, 16.9% of left their position over an 11-month period and a majority of reported moderate to high levels of emotional exhaustion. No association was found between any dimension of burnout and odds of turnover; however, burnout may have other negative consequences for both neonatal intensive care nurses and infants, and merits further exploration.